Pedagogical implications of Vincent Granat's personalistic humanism - Sławomir Chrost (Nicolaus Copernicus University in Toruń, 2016)
The Servant of God Father. prof. Wincenty Granat was one of the representatives of the Christian personalism mainstream, showing the central role of the human due to the will of God (theological theme) and the ontological uniqueness (philosophical theme). In Granat's personalist Christian humanism one can observe something that can be conventionally called anthropological-theistic parallelism, where God poses a human in the center of His interest, and the selfsame has only to repay all its temporal reference to the Transcendent. This has some educational consequences. An educator deals with the conditions and methods of personality education, and therefore mainly takes into account its activity (love), autonomy (freedom), plasticity (transformation), and capacity of evaluation (true). According to Granat the Catholic personalism in education will strongly emphasize the humanistic education and the development of self-reliance, will require individual treatment to pupils, and will stimulate sense of responsibility and honour. The belief that a man is not only a member of the nation, the state, the Church, but above all he/she is a person and has an aim to achieve in eternity, must emotionally grow into the ward's psyche.